Plasmodium-encoded murine IL-6 impairs liver stage infection and elicits long-lasting sterilizing immunity - Belhimeur, Selma; Briquet, Sylvie; Peronet, Roger; Pham, Jennifer; Commere, Pierre-Henri; Formaglio, Pauline; Amino, Rogerio; Scherf, Artur; Silvie, Olivier; Mecheri, Salaheddine (Frontiers in Immunology, 2023)
Plasmodium sporozoites inoculated by Anopheles mosquitoes into the skin of the mammalian host migrate to the liver before infecting hepatocytes. Previous work demonstrated that early production of IL-6 in the liver is detrimental for the parasite growth, contributing to the acquisition of a long-lasting immune protection after immunization with live attenuated parasites. Considering that IL-6 as a critical pro-inflammatory signal, we explored a novel approach whereby the parasite itself encodes for the murine IL-6 gene. We generated transgenic P. berghei parasites that express murine IL-6 during liver stage development. Though IL-6 transgenic sporozoites developed into exo-erythrocytic forms in hepatocytes in vitro and in vivo, these parasites were not capable of inducing a blood stage infection in mice. Furthermore, immunization of mice with transgenic IL-6-expressing P. berghei sporozoites elicited a long-lasting CD8+ T cell-mediated protective immunity against a subsequent infectious sporozoite challenge. Collectively, this study demonstrates that parasite-encoded IL-6 attenuates parasite virulence with abortive liver stage of Plasmodium infection, forming the basis of a novel suicide vaccine strategy to elicit protective antimalarial immunity.